The use of a durable right ventricular assist device for isolated right ventricular failure due to combined pre- and postcapillary pulmonary hypertension. (May 2019) - Vullaganti, Sirish; Tibrewala, Anjan; Rich, Jonathan D.; Pham, Duc T.; Rich, Stuart
Patients with isolated right ventricular (RV) failure have poor outcomes and minimal treatment options. We report a case where a durable RV assist device (RVAD) was implanted for end-stage RV failure from combined pre- and postcapillary pulmonary hypertension (PH) due in part to chronic thromboembolic PH using a temporary percutaneous RVAD as a bridging strategy. While the patient ultimately died from non-cardiovascular causes, there was significant improvement in markers of cardiogenic shock and hemodynamic RV function parameters without adverse effects from increased pulmonary artery pressures. More research is needed to identify an appropriate long-term mechanical support strategy for this patient population.